Peningkatan Partisipasi Masyarakat melalui Sosialisasi Informasi Nuklir di Kabupaten Bangka Selatan dan Bangka Barat - Suhardi Suhardi; Maera Zasari (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2014)
The issue of the government's plan to realize the construction of a nuclear power plant (PLTN) in the Bangka Belitung Islands Province is still a hot topic of discussion among the community, especially in the South Bangka and West Bangka districts. Receiving unbalanced information about nuclear in the community affects the formation of perceptions that grow and develop among the public towards nuclear science and technology. This perception will affect public acceptance both positively and negatively and will then be communicated when facing actual problems. Through nuclear information socialization activities, it is hoped that it can increase public knowledge/insight and understanding of nuclear, especially in the South Bangka and West Bangka Regencies. Nuclear information socialization activities carried out include: (1) practical learning of nuclear information and (2) visits to nuclear facilities. Based on the information dissemination activities that have been carried out, it is obtained that (1) the community in South Bangka and West Bangka Regencies gain knowledge/insight and understanding of nuclear information and (2) the knowledge/insight and understanding of the community in South Bangka and West Bangka Regencies about nuclear information began to increase.